Socio-Cultural : Dalam Perdebatan Penundukan Prajurit TNI dalam Peradilan Umum dengan Peradilan Militer - Irman Putra; Arief Fahmi Lubis (Public Service and Governance Journal, 2020)
Pros and cons about the position and jurisdiction of military courts still often occur in legal discourse in Indonesia. On the one hand, there is a group that states that the military court is only authorized to try military crimes and is not authorized to try general crimes committed by TNI soldiers, but another group states that the military court still has the authority to try both general crimes and military crimes. This article will photograph the discourse that has existed so far. This article will also explain the Position and Jurisdiction of the Military Court in Indonesia after being under the jurisdiction of the Supreme Court and the impact of the submission of TNI soldiers to the General Court on military principles. The method used was an in-depth interview with a number of sources, especially to see the growing opinion if TNI soldiers were tried in the general court. The conclusion of this article is that psychologically and culturally, TNI soldiers are not appropriate to be tried in the general court. Thus, the issue of subjugating TNI soldiers to the general court is not only juridical but also psychological and cultural. In addition, if TNI Soldiers are subject to the general judiciary, it will result in the destruction of military joints or principles that are the backbone of law enforcement and discipline of Soldiers.